The 2004 guide to the evaluation of educational experiences in the armed services (American Council On Education, 2004)
For more than a hald century, the Guide to the Evaluation of Education Experiences in the Armed Services has been the standard reference work for recognizing learning acquired in military life. Since 1942, ACE and has worked cooperatively with the US Department of Defense, the Armed Services, and the US Coast Guard in helping hundreds of thousands of individuals earn academic credit for learning achieved while serving their country.